Bioethanol Production From Waste Potatoes Using Bacterium Zymomonas Mobilis Mtcc 2427 (Applied Biological Research, 2013)
The present study was carried out to assess bioethanol production from waste  potatoes and optimize some fermentation variables for Zymomonas mobilis MTCC 2427. The waste potatoes contained 76% starch. Under solid state  fermentation (SSF) maximum bioethanol of 14.17 g 100 mL-1 medium was  achieved at 35°C when incubated for 120 hr. Under simultaneoussaccharification  and fermentation (SiSF), highest ethanol yield of 14.36 g 100 mL-1 medium was  attained at 35°C, pH 5.5 and 120 hr. The ethanol produced was volatile,  flammable, colourless and miscible in water and organic solvents having pleasant smell. SiSF fermentation gave more ethanol recovery than SSF method.
Keywords: Bioethanol; biofuels; SiSF; fermentation; potato; Zymomonas mobilis